2015
DOI: 10.1002/jcsm.12031
|View full text |Cite
|
Sign up to set email alerts
|

Activin-βCmodulates cachexia by repressing the ubiquitin-proteasome and autophagic degradation pathways

Abstract: BackgroundCancer-associated cachexia and muscle wasting are considered key determinants of cancer-related death and reduction in the quality of life of cancer patients. A crucial link has been established between activin signaling and skeletal muscle atrophy-hypertrophy.We previously showed that activin-βC, a novel activin-A antagonist, is a tumor modulator that abolishes the cancer-associated cachexia in a mouse genetic model of gonadal tumorigenesis, in which the normal balance of inhibin/activin signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…[87, 88] The common metabolic abnormalities to cancer cachexia and sarcopenia include altered hormone levels, elevated cytokines, increased insulin resistance, increased muscle proteolysis, elevated acute phase proteins, and altered nutrient utilization. [87] Many experts believe, however, that muscle loss in cancer is a more active process, mediated by a number of pro-inflammatory cytokines, as well as members of the TGFβ-superfamily including activins[89] and myostatin. [90, 91]…”
Section: 0 Muscle Weakness In Cancermentioning
confidence: 99%
“…[87, 88] The common metabolic abnormalities to cancer cachexia and sarcopenia include altered hormone levels, elevated cytokines, increased insulin resistance, increased muscle proteolysis, elevated acute phase proteins, and altered nutrient utilization. [87] Many experts believe, however, that muscle loss in cancer is a more active process, mediated by a number of pro-inflammatory cytokines, as well as members of the TGFβ-superfamily including activins[89] and myostatin. [90, 91]…”
Section: 0 Muscle Weakness In Cancermentioning
confidence: 99%
“…They impressively showed that NF‐κB is activated in cachectic muscle in both paired box 7 progenitor cells and myofibers . Other studies buttress the view that increased forkhead box protein O (FoxO) signalling and the activation of the transcription factors NF‐κB, muscle RING finger 1 (MuRF1), and muscle atrophy F‐box (MAFbx) in skeletal muscle play major roles during cachexia onset and progression . MuRF1 and MAFbx are essentially involved in muscle atrophy development.…”
Section: Basic Sciencementioning
confidence: 99%
“…15,16 Other studies buttress the view that increased forkhead box protein O (FoxO) signalling and the activation of the transcription factors NF-κB, muscle RING finger 1 (MuRF1), and muscle atrophy F-box (MAFbx) in skeletal muscle play major roles during cachexia onset and progression. [17][18][19] MuRF1 and MAFbx are essentially involved in muscle atrophy development. Indeed, genes whose expression levels are commonly increased during multiple models of skeletal muscle atrophy, including cancer and sepsis, are MAFbx, MuRF1, and cathepsin, and there is evidence that each is a FoxO target gene.…”
Section: Basic Sciencementioning
confidence: 99%
“…He impressively showed that NF‐κB is activated in cachectic muscle in both PAX 7 progenitor cells and myofibers . Other studies buttress the view that increased forkhead box protein O (FoxO) signalling and the activation of the transcription factors NF‐κB, MuRF1 and muscle atrophy F‐box (MAFbx) in skeletal muscle play major roles during cachexia onset and progression . MuRF1 and MAFbx are essentially involved in muscle atrophy development.…”
Section: Basic Sciencementioning
confidence: 99%